Review on multiobjective evolutionary algorithms and application in metal matrix composites - Yevseyeva, I.; Vitor Basto-Fernandes; Grácio, José (International Review of Mechanical Engineering, 2012)
This work presents a review on evolutionary algorithms when applied to problems with multiple objectives to be optimized simultaneously. Evolutionary algorithms are well-known optimization techniques utilized in situations where exact methods fail, in particular, in case of optimization of complex, non-convex, non-differentiable, non-smooth and/or discontinuous functions that are common to the real engineering applications, or used for solving combinatorial NP-hard problems, for instance encountered in the search of optimal combination of several parameters. These techniques are shown to be efficient in finding at least sub-optimal solution(s) when solving problems of mentioned complexity. In this work, the recent multiobjective evolutionary algorithms are presented and the potential application of multiobjective evolutionary algorithms in product development is illustrated.